Exploring the relationship between manager profile and management control: Evidence from Moroccan Manufacturing Companies - Hammouch, Hind (PT. Riset Press International, 2024)
This study examines the impact of managerial profile on management control in Moroccan manufacturing companies, using a method of analysis based on correlation and multivariate regression. The independent variables include the manager's age, experience and training, while management control is considered the dependent variable. By exploring these relationships, the study aims to identify the specific influences of managers' individual traits on the design and implementation of management control systems in this particular context. The expected results will contribute to enriching strategic management practices by providing valuable insights for practitioners and researchers interested in corporate governance and organizational performance.